2022
DOI: 10.3389/fimmu.2022.1015775
|View full text |Cite
|
Sign up to set email alerts
|

Neglected mycobiome in HIV infection: Alterations, common fungal diseases and antifungal immunity

Abstract: Human immunodeficiency virus (HIV) infection might have effects on both the human bacteriome and mycobiome. Although many studies have focused on alteration of the bacteriome in HIV infection, only a handful of studies have also characterized the composition of the mycobiome in HIV-infected individuals. Studies have shown that compromised immunity in HIV infection might contribute to the development of opportunistic fungal infections. Despite effective antiretroviral therapy (ART), opportunistic fungal infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 165 publications
(193 reference statements)
0
2
0
Order By: Relevance
“…Disrupting the fungal environment has been shown to cause irritable bowel syndrome, coeliac disease, and pancreatic disorders, displaying the importance that these fungi play in maintaining one’s health [ 34 ]. Disruptions by viruses such as hepatitis B and HIV even affect systems outside of the gastrointestinal tract, specifically the immune and hepatic systems, which can cause extensive disease and morbidity [ 35 , 36 ]. There are harmful fungi that can disrupt the gastrointestinal tract that have also been linked to disease, such as how an increase in Malassezia restricta is linked with Crohn’s disease and inflammatory bowel disease [ 37 , 38 ].…”
Section: Gut Mycobiomementioning
confidence: 99%
“…Disrupting the fungal environment has been shown to cause irritable bowel syndrome, coeliac disease, and pancreatic disorders, displaying the importance that these fungi play in maintaining one’s health [ 34 ]. Disruptions by viruses such as hepatitis B and HIV even affect systems outside of the gastrointestinal tract, specifically the immune and hepatic systems, which can cause extensive disease and morbidity [ 35 , 36 ]. There are harmful fungi that can disrupt the gastrointestinal tract that have also been linked to disease, such as how an increase in Malassezia restricta is linked with Crohn’s disease and inflammatory bowel disease [ 37 , 38 ].…”
Section: Gut Mycobiomementioning
confidence: 99%
“…These alterations are commonly referred to as microbial dysbiosis. Collectively, studies in adults PLWH (ALWH) have shown a decrease in bacterial ( 12 ) and fungal diversity ( 15 , 16 ), an expansion of the virome ( 9 , 17 ), an increase in pathobionts and a decrease in anti-inflammatory commensals ( 14 ), compared with seronegative individuals. Microbial dysbiosis is partially restored by ART.…”
Section: Introductionmentioning
confidence: 99%